Effects Of Fermentation, Drying And Additional Of Carotene Oil On Nutritional Value Of Cassava Flour - Razali, Rozaihan (2007)

(untitled)
Population drift from rural to urban areas has increased the demand ready to eat traditional processed food. Thus, there is a great need for better ways of preparing this food at both domestic and factory scale. Cassava ranks fourth in crops importance in the world and various types of traditional foods are locally made from it especially in the tropics. However, cassava is low in vitamins and minerals content. In addition, it contains cyanogenic glycosides which are known to be toxic because the glycosides yield hydrogen cyanide (HCN) when enzymically degraded. Thus, the most important requirement in the processing of cassava roots is its detoxification by the reduction of the total cyanide content (bound and free) to acceptable levels. Furthermore, the conventional methods used previously have not necessarily detoxified the final products sufficiently for safe consumption. The field of study is process development and the research issue is the development of safe processes to for the manufacture of indigenous food containing toxins. The development of new processes to reduce cyanogen from cassava flour using fermentation and drying processes can be easily done in a well equipped laboratory. The process in the present study adopted the conventional gari (most popular traditional food for Nigerians) making process with some modifications. The new process consists of fermentation in a bioreactor, drying using a fluidized bed dryer and fortification by carotene oil in order to reduce the cyanide content of the final product of cassava flour and at the same time, fortifying it with ß-carotene. It was found that the overall process flow sheet is improved, and the processing time is reduced. The cassava flour obtained was free from cyanide content and successfully fortified with ß-carotene. Fermentation time was improved during which the sour flavor and desired aroma was achieved within 20 h as compared to 2 days under conventional technique. Removal of hydrogen cyanide was facilitated by drying for 15 minutes at 80 ºC, while reducing moisture content to acceptable level. Drying step had also improved the process flow sheet with shorter duration and ease of handling continuously. The fortification of the fermented cassava flour with ß-carotene was also successful. On the other hand, with the present methods used to produce cassava flour, risks associated with conventional and some industrial scale of cassava processing techniques and its products were removed. With a better control over processing conditions such as time and temperature, higher quality of cassava flour may be guaranteed.